2021
DOI: 10.1111/jors.12541
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and the uneven geography of the first wave of the COVID‐19 pandemic

Abstract: This paper examines the uneven geography of COVID-19-related excess mortality during the first wave of the pandemic in Europe, before assessing the factors behind the geographical differences in impact. The analysis of 206 regions across 23 European countries reveals a distinct COVID-19 geography. Excess deaths were concentrated in a limited number of regions -expected deaths exceeded 20% in just 16 regions-with more than 40% of the regions considered experiencing no excess mortality during the first six month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 56 publications
1
60
0
1
Order By: Relevance
“…But recent studies have shown that although the number of doctors and beds per capita was high, the scale of the epidemic meant that these high levels of health infrastructure were still insufficient. Furthermore, the overconfidence that developed countries had in their health systems had deleterious effects because they were ill-prepared for the coming wave (Rodríguez-Pose, & Burlina, 2021 ). They thought that the high level of health services would be sufficient to absorb the pandemic waves, but this was not the case (Gudi & Tiwari, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…But recent studies have shown that although the number of doctors and beds per capita was high, the scale of the epidemic meant that these high levels of health infrastructure were still insufficient. Furthermore, the overconfidence that developed countries had in their health systems had deleterious effects because they were ill-prepared for the coming wave (Rodríguez-Pose, & Burlina, 2021 ). They thought that the high level of health services would be sufficient to absorb the pandemic waves, but this was not the case (Gudi & Tiwari, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Others have investigated the spread of contagion and health risks in relation to the endogenous aspects of the “attack rate” that can be affected by the characteristics of an economy (for instance its integration with the rest of the country and the world, age structure of the population, etc.) and of the respective institutions, such as the organization and functioning of the health system ( Ferrari et al, 2020 , Khairulbahri, 2021 , Kumar et al, 2021 , Rodríguez‐Pose and Burlina, 2021 ). Still others have focused on the differential impact of the pandemic between territories, regions and countries (Arbolino & Caro, 2021; Carnazza & Liberati, 2021 ; OECD, 2020 ).…”
Section: The Issue: Modelling the Impact Of Policy Responses To The P...mentioning
confidence: 99%
“…The distribution of the accounting noise might depend on countries’ level of wealth, since wealthier countries might be in a better position to manage the monitoring process and bear the related costs. To check whether our estimates are affected by a possible misreporting of mortality data, we follow Rodriguez-Pose and Burlina ( 2021 ) and we calculate the excess mortality rate as the difference between logDEATH and the (log) average death rate in 2016–18, provided by the World Bank’s World Development Indicators. Such an index is considered more reliable than the standard death rate because it compares actual COVID-19 deaths with the expected death rate in a period where no other pandemics have been reported.…”
Section: Robustness Testsmentioning
confidence: 99%